Demystifying buprenorphine misuse: Has fear of diversion gotten in the way of addressing the opioid crisis?. Issue 2 (3rd April 2019) - Doernberg, Molly; Krawczyk, Noa; Agus, Deborah; Fingerhood, Michael
Abstract: Buprenorphine is considered one of the most effective treatments for opioid use disorder and significantly reduces risk of overdose death. However, concerns about its diversion and misuse have often taken center stage in public discourse and in the design of practices and policies regarding its use. This has been to the detriment of many vulnerable patient populations, especially those involved in the criminal justice system. Policies that restrict access to buprenorphine in criminal justice and other settings due to concerns of diversion do not accurately reflect the relative risks and safety profile associated with it, creating unnecessary barriers that drive an illicit market of this much-needed medication. Although proper regulation of all controlled medications should be a priority, in most instances the benefits of buprenorphine highly outweigh its risks. In the midst of a national crisis, efforts should be focused on expanding, and not restricting, access to this lifesaving treatment.